Razlike v telesni zmogljivosti slovenskih srednješolcev - Kovač, Marjeta (Šport (Ljubljana), 2013)
The study aimed to establish differences in the body characteristics and motorabilities of secondary school students in terms of gender, age and type of school programme. The data from sport-education records were used to assess their physical abilities. The sample included 13,069 male and 11,364 female secondary school students attending different secondary school programmes (gymnasium, secondary technical school and vocational school) in the 2011/2012 school-year. The students attending gymnasium have higher physical abilities than their counterparts in the secondary-technical programme, where as the latter are better than their counterparts in vocational schools. The differences among the studied groups in terms of physical ability are explained best by age, followed by school programme and subjects' age. The differences in physical characteristics and motor abilities among the secondary school students attending different programmes are smaller with male and larger with female students. The biggest differences among the secondary school students attending different programmes are visible in the tests of sit-ups, standing broad jump and 600-metre run. Those students who attend technical and vocational programmes need at least three hours of physical education a week and more possibilities to join extra-curricular and school sport programmes.
Keywords: age; gender; gibalne sposobnosti; motor abilities; physical characteristics; secondary school programmes; spol; sport; srednješolci; srednješolski programi; starost; šport; telesne značilnosti